PENGEMBANGAN KREATIVITAS SISWA SEKOLAH DASAR MELALUI PEMBELAJARAN MATEMATIKA OPEN-ENDED - Hendra Erik Rudyanto (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2013)
Creativity of learners has become more and more important in the era of glabal competition, because the complexity of problems of all aspects in the modern era keeps on increasing all the time. The teaching and learning mathematics at the elementary school has to give the positive contribution so as to encourage the students’ creativity as optimally as possible. Open ended technique of teaching and learning mathematics can assumptively give alternatives of the ‘true’ solutions to students by experiencing investigation against mathematic problems using their deep thnking skill, so that they can construct alternatives of solution creatively. Key words:   Creativity, Open Ended Technique of Teaching and Learning Mathematics